Teachers' Perceptions of Curriculum Changes - Erna Zamasi (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
The curriculum is an important aspect in the educational framework. The curriculum acts as an educational guide. Therefore, the curriculum will continue to develop along with the times and the needs of society. As it is now, the curriculum has undergone improvements from the 2013 Curriculum to the Independent Learning Curriculum. These changes certainly have an impact on teachers as implementers. Therefore, this research aims to find out how teachers perceive curriculum changes. To collect data, this research uses an interview method by asking several relevant questions. The results of the interview are presented in a descriptive explanation. From the results of interviews regarding changes to the curriculum, it can be seen that the 2013 Curriculum and the Merdeka Belajar Curriculum have many differences, especially in the aims of the curriculum focus. In their perception, the new curriculum has advantages, especially because it gives teachers freedom to manage learning while encouraging student activity. The weaknesses that teachers need to pay attention to are limited teacher resources and learning media/devices. As a solution there must be an increase in teacher resources and learning tools.